MEDB-78. Unified rhombic lip origins of Group 3 and Group 4 medulloblastoma. (3rd June 2022) - Smith, Kyle; Bihannic, Laure; Gudenas, Brian; Gao, Qingsong; Haldipur, Parthiv; Tao, Ran; Iskusnykh, Igor; Chizhikov, Viktor; Scoggins, Matthew; Zhang, Silu; Edwards, Angela; Deng, Mei; et al.
Abstract: Identification and characterization of lineage-specific beginnings of distinct medulloblastoma (MB) subgroups is a fundamental challenge in the field. Genetically engineered mouse models and cross-species transcriptomics have provided mounting evidence of discrete, subgroup-specific developmental origins. Likewise, murine single-cell transcriptional atlases of cerebellar development have recently provided further clues into MB subgroup origins, particularly for poorly defined Group 3 and Group 4-MB. However, initial studies were underpowered to characterize rare populations and lacked robust validation, resulting in incomplete findings. Herein, we leveraged a large harmonized murine cerebellar atlas, targeted lineage enrichment, and integrative multi-omic strategies to deeply dissect MB origins. Isolation of spatially and temporally discrete developmental trajectories of key glutamatergic lineages born out of the murine upper rhombic lip provided an enhanced reference for mapping MB subgroup origins, especially for Group 3 and Group 4-MB. However, human-specific anatomic and cellular complexity, particularly within the rhombic lip germinal zone complicated murine-derived inferences. Further tumor-normal integrations using a novel single-cell atlas of the human fetal cerebellum, companioned with laser-capture micro-dissected transcriptional and epigenetic datasets, reinforced developmental insights extracted from candidate murine cerebellar lineages. Characterization of compartment-specific transcriptional signatures identified in the human upper rhombic lip implicated convergent cellular correlates of Group 3 and Group 4-MB, suggestive of a common developmental trajectory underlying their ancestry. Systematic imaging review and 3D summarization of a large clinical trial series of patient tumors, coupled with our advanced insights into developmental signatures, substantiated subgroup-specific tumor location patterns observed at diagnosis. Together, our results strongly implicate a common lineage trajectory of the upper rhombic lip as the probable origin of Group 3 and Group 4-MB. These important findings provide unprecedented opportunities to explore context-dependent mechanisms of MB pathogenesis and will foster generation of improved preclinical models that more faithfully recapitulate tumor biology.